Nutritional Awareness of Undergraduate Healthcare Students - Friebohle, Lisa; Ward, Maggie; Habtemariam, Maryon (KHD-Production, 2023)
Overweight and obesity rates are an epidemic in the United States (U.S.) with these rates increasing dramatically in recent decades (Sogari et al., 2018). According to McEligot et al. (2020) college students classified as overweight and/or obese in the U.S. increased from 29% to 32.5% from 2000 to 2009. College is a critical time for young adults in terms of dietary choices and the relationship between students and weight gain. The purpose of this DNP project was to assess if undergraduate healthcare students in the Midwest showed poor nutritional dietary habits and showed a willingness to change their poor habits for a healthier lifestyle. The data would be used to assist the college healthcare clinic in providing proper nutritional awareness and guidance for the students. Undergraduate nursing students at a Midwest university completed an assessment tool, in the form of a 16-question Rapid Eating and Activity Assessment for Patients, Abbreviated Version (REAPS) survey that assessed their knowledge regarding nutrition and their food choices. Each question had a numeric scale (1-3) scoring system with defined results. The descriptive statistics tool in SPSS was used for analysis of the survey results. This study showed that 62.43% of the responses from undergraduate nursing students that were surveyed had poor dietary habits. 96.29% of the students that were surveyed did have a willingness to change in order to have a healthier lifestyle. Undergraduate healthcare students would benefit from increased nutritional awareness while on and off campus. The college health clinic can help promote a healthy lifestyle and decrease obesity related illnesses for students. There are numerous opportunities for colleges to promote nutritional awareness among their student body.